WORK FROM HOME (WFH) POLICIES ARE BEING IMPLEMENTED AT THE BANDUNG CITY PUBLIC WORKS DEPARTMENT - Aep Saepudin; M Dana Prihadi; Tuti Asmala; Muhammad Yusuf (Lembaga Pengkajian Dan Pengembangan Sumberdaya Pembangunan (lppsp), 2022)
National policy is critical to a policy's success. Policy implementation has a broad spectrum of implications and conditions. This study aims to investigate and describe the implementation of work-from-home (WFH) policies at the Bandung Regency Public Work Services Office. In this study, the qualitative research method was used. The findings of this study indicate that the implementation of the Work From Home Policy at the Public Works Services Office of Bandung City has been successful in meeting spatial aspects, specifically in the form of transforming personal space or employee homes in the Public Works Services Office of Bandung City by maximizing various existing devices and technologies that are considered convenient to use. Bandung City Public Work Services Office employees have been able to adapt to two different time situations, cyclical time and linear time. This demonstrates that the office and family support is adequate to meet the time constraints. Meanwhile, the Bandung City Public Work Services Office has been able to provide good work productivity by aligning narrative writing roles as employees, husbands or wives, and family members.